AUDITOR ETHICS MODERATE THE EFFECT OF EXPERIENCE, COMPETENCE, INDEPENDENCE, ON AUDIT QUALITY - Saputra, Mohammad Fajar; J.B Amiranto (GEMAH RIPAH: Jurnal Bisnis, 2025)
The purpose of this research is to investigate how auditor ethics affect audit quality as a moderating factor. This study aimed to show that auditor ethics is a fundamental trait that auditors must have in order to conduct high-quality audits. Out of the 63 questionnaires distributed to auditors across all levels, from junior to partner, only 60 were deemed valid for analysis. Hypothesis testing was conducted using the Outer Model and Inner Model tests within the SmartPLS application. The findings revealed that auditor ethics, as a moderating factor, could either strengthen or weaken the connection between the analyzed parameters and audit quality. The results also indicate that auditor independence, competence, and safety can uphold audit quality even without the presence of auditor ethics. Consequently, auditors can provide high-quality audits without relying solely on ethical considerations.